Die normative Bedeutung der Handlungsfolgen nach Thomas von Aquin - Hofmann, Stefan (Theologie und Philosophie, 2020)
It is customary for ethicists to emphasize that moral judgments about human actions have to be made in the light of the consequences of these actions. Consequentialists argue that the moral status of an action is completely dependent on the goodness of its consequences. Deontological ethicists try to show that their theories do in fact recognize the importance of consequences. This article presents and analyzes Thomas Aquinas’s thinking about consequences. It shows that Aquinas clearly distinguishes between different kinds of consequences: effectus per se, effectus per accidens, and eventus sequens. The importance of these distinctions within Aquinas’s theory of action has been overlooked by proportionalists but also by Thomistic authors. Hence, the article tries to give a systematic account of Aquinas’s concept of consequences and of the normative weight these different types of consequences acquire in his theory of moral judgments. Finally, the article specifies how contemporary ethical debate about consequences could benefit from Aquinas.